The Importance Of Organic-Mineral Fertilizer Standards In Preserving The Agrochemical Properties Of Soil (Texas Journal of Agriculture and Biological Sciences, 2024)
The article presents information about changes in the amount of mobile nutrients in the soil when applying organomineral fertilizers in different types and standards in the care of sunflower crops. At the same time, the most optimal results in terms of the dynamics of improvement of nutrients in the soil were achieved using combinations of the preparations Ecogum bio, Ecosil + Ecogum AF + Polybor and Ecosil + Ecogum complex + Ecogum FC + Polybor